2009
DOI: 10.1590/s1984-46702009000200006
|View full text |Cite
|
Sign up to set email alerts
|

Teste do efeito de borda na predação de ninhos naturais e artificiais no Cerrado

Abstract: ABSTRACT. A test of the edge effect on predation of natural and artificial bird nests in the Cerrado. The Cerrado is still one of the most important ecosystems in Brazil, even though more than 50% of its area has been altered or converted to pastureland and plantations. Despite its intense degradation, few ecological processes that might affect its biodiversity have been evaluated. The goal of this study was to test the edge effect on the predation rates at natural and artificial nests, at the Ecological Stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 56 publications
3
13
0
4
Order By: Relevance
“…A previous study showed similar tendency for large eggs (quail eggs; França & Marini 2009a). Surprisingly, studies of natural nests in the same region found declining nest survival rates as the breeding season progressed (Borges & Marini 2010, Santos 2008.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…A previous study showed similar tendency for large eggs (quail eggs; França & Marini 2009a). Surprisingly, studies of natural nests in the same region found declining nest survival rates as the breeding season progressed (Borges & Marini 2010, Santos 2008.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast, in some areas in the Cerrado, birds were the main predators (França et al 2009). Overall, predation in the Cerrado habitats tended to increase throughout the reproductive period (Borges & Marini 2010), decrease during nest development (França & Marini 2009b), and differ between habitats and microhabitats (França & Marini 2009a, Borges & Marini 2010. These studies show the importance of predation for population dynamics of neotropical birds and so experiments with artificial nests may be important to understand spatial and temporal patterns of reproductive success.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations